Participation of Clients in the E-Banking Practices of Nepalese Commercial Banks - Sah, Rajesh Kumar; Karn, Binod Lal; Sahani, Suresh Kumar (Mikailalsys Journal of Advanced Engineering International, 2025)
The aim of present research was to analyze the different e-banking services provided by Nepalese commercial bank in terms of customers’ participation. Nowadays, almost all commercial banks and financial intermediaries provide internet banking services for their customers in order to reduce cost and time. This study conducted to understand the different technological advancement used by the Nepalese commercial bank in their day-to-day operation. Data for this research came from both primary and secondary sources: responses from a questionnaire and many secondary sources. Present investigation was conducted utilizing a survey technique using a questionnaire as the data collecting tool. To get understanding of consumers' involvement in the Nepalese banking sector, structured sets of questions including Likert scale questions, yes/no questions, multiple choice questions were asked. According to the findings of this study, decision-makers should take into consideration the importance of centering their attention on the alertness, and faith of clients. This can be accomplished by enhancing safety measures, implementing proper e-legislation, and offering electronic bills or assurance for each and every transaction. The ultimate goal is to instill a greater sense of confidence in those who use such services and to encourage a culture of internet banking usage throughout Nepal. The findings of this study indicate that both the environment in which the application for online banking is used and the program itself are in need of further enhancement. The bank should always place a strong emphasis on encouraging consumer participation in the use of online banking services, rather than only focusing on the implementation of latest technological advancements.